A Review of Clinical Research Trends in Korean Medicine for the Treatment of Dupuytren’s Contracture - You Jin Heo; Eun Yong Lee; Cham Kyul Lee; Seung Yeon Lee; Jeong-Du Roh; Na Young Jo; Jung Won Byun; Su Min Jeong (Journal of Acupuncture Research)
This study aims to analyze the clinical research trends in traditional Korean medicine treatments for Dupuytren’s contracture, focusing on the effectiveness and outcomes of various interventions. The search was performed using six databases, and five studies were selected and analyzed after exclusion based on specific criteria. In the included studies, 29 fingers of 20 individuals were selected and classified according to the journal, publication year, patient information, treatment, and evaluation methods. The treatment interventions included acupuncture, moxibustion, herbal medicine, bee venom pharmacopuncture, and Pi needle therapy. Various assessment methods were used to evaluate the outcomes, including pain scores, range of motion, grip strength, and patient satisfaction. The findings of this study revealed that traditional Korean medicine treatments for Dupuytren’s contracture are effective in reducing the severity of the contracture and improving patient outcomes. However, future studies should aim to standardize treatment protocols and expand the assessment of their long-term effects.